Impact of Corporate Governance on the Performance of Selected Banks in Nigeria: Array - Adedeji, Elijah Adeyinka; Olajide, Ajulo Benjamin (The Journal of Accounting and Management, 2021)
The impact of corporate governance on the performance of selected banks in Nigeria has become a wide-reaching truism that the quality of corporate governance makes a significant difference to and has a chief effect on the performance of banks. Effective corporate governance requires a clear understanding of the respective role of the board and of senior management and their relationships with others in the corporate structure. This study aim to examine the relationship that exists between corporate governance and banks performance of selected commercial banks in Nigeria. Using regression analysis of 5 years ranging from 2014 – 2018. The stock performance being the response variable was captured by Market price per share (MPS) while the explanatory variables included Board Size (BS), Corporate Governance Disclosure Index (CGDI), Non-Executive Director (NED) and Number of Female Director (NUM) are the regressors used in achieving this objective. Descriptive analysis was used to ascertain the mean (1.64141; MPS, 2.658831; BS, 2.145323; NED, 1.127043; NUM 0.933143; CGDI) median, Maximum, Minimum. Correlation was carried out and a positive and strong relationship were generated. Post estimation diagnostic test of Hausman test and redundant fixed effect test were adopted in selecting the most appropriate model to capture the impact of corporate governance characteristics on stock performance of banks. The test indicated that random effect is not an appropriate model and non-normality of the variables will not encourage the use of ordinary effect, therefore, in estimating the parsimonious model of the variable, fixed effect will be an appropriate assumption. 86.78% of the stock performance of banks was accounted for by the explanatory variables The work suggests that efforts should be made to improve corporate governance focus on the stock performance of deposit money banks since the stock performance is a measure of the wealth of shareholders. Also, the Central bank of Nigeria and other relevant authorities should also try to ensure that steps are taken for mandatory and absolute compliance with the code of corporate governance. Also, an effective legal framework should be developed that specifies the rights and obligations of a bank, its directors, shareholders, specific disclosure requirements and provide for effective enforcement of the law.